2018
DOI: 10.1136/gutjnl-2018-315994
|View full text |Cite
|
Sign up to set email alerts
|

Human CPA1 mutation causes digestive enzyme misfolding and chronic pancreatitis in mice

Abstract: The results offer categorical evidence that mutations elicit enzyme misfolding and cause chronic pancreatitis via an ER stress-related mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 10 publications
0
49
0
1
Order By: Relevance
“…This study showed that CPA1 N256K knock-in mice harboring the most frequent p.N256K human CPA1 mutation develop spontaneous and progressive CP and exhibit signs of ER stress in their pancreas. 56…”
Section: Mis-folding-associated Prss1 Mutationsmentioning
confidence: 99%
“…This study showed that CPA1 N256K knock-in mice harboring the most frequent p.N256K human CPA1 mutation develop spontaneous and progressive CP and exhibit signs of ER stress in their pancreas. 56…”
Section: Mis-folding-associated Prss1 Mutationsmentioning
confidence: 99%
“…Consistent with these data, it was recently shown that pancreatitis stimuli in human acinar cells reduces protective XBP1s signaling and in turn upregulates CHOP, cell damage, and activation of inflammatory signaling (12). In the past several years, mutations associated with digestive enzyme misfolding have been identified that, when introduced in mouse models, induce ER stress responses and exhibit spontaneous CP (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Importantly, patients with CP are at a higher risk for pancreatic cancer, one of the most devastating diseases. The main clinical manifestations of CP are abdominal pain, indigestion, steatorrhea and diabetes.…”
Section: Introductionmentioning
confidence: 99%